Breaking the 'One-Size-Fits-All' Paradigm: The Impact of MI Theory on Student Self-Efficacy and Inclusion in school Education - Chandan Pal Singh; Yerzhan Kerimbekov; Manju Khari (Emerging Frontiers Library for The American Journal of Management and Economics Innovations, 2025)
There are multiple ways of learning and knowing. Each brain has a profile of Multiple Intelligence. Theory of Gardner's Multiple Intelligence provides a more holistic and natural profile of human potential. Success of any education system depends upon its own curriculum. The present curriculum for school education doesn't satisfy the needs of all students who possess different sets of Intellectual strengths and weakness. Students with dyslexia, dysgraphia, dyscalculia and slow learners are looked upon as hapless children. So the common school curriculum at present needs a lot of physical adaptations in designing curriculum for inclusive education. Inclusive education is an approach to address the learning needs of all children with a specific focus on those who are vulnerable to marginalization and exclusion. Hence, there is an immediate need for inclusive education. Is it possible to have inclusive education in the present school curriculum? Of course, it is a challenging task for the educationists, professionals and curriculum constructors to bring out an innovative school curriculum to promote inclusive education. So, in the present article the authors suggest that multiple intelligences based common school curriculum allows a wider range of students to successfully participate in mainstream classroom learning and thus enhancing inclusive education at school level.